Control of ovulation - Crighton, D. B. (Butterworths, 1978)
Control of Ovulation discusses the general principles and practical applications of ovulation control. The book presents 25 papers that cover the basic research practices and practicalities of ovulation control. The materials are grouped according to their respective themes. The first three parts cover the hypothalamus, pituitary gland, and ovary, respectively. The remaining papers discuss concerns regarding the applications of ovulation control, such as ovulation failure; diagnosis of ovulatory disorders; and the induction and synchronization of ovulation. The text will be of great use to pra.